Persistence of airborne tree pollen from the Cupressaceae family during the last decade in the city of Bahia Blanca - Ramon, German D. (2022)
Airborne pollen is a major contributor to allergic respiratory diseases. However, the literature on patterns and seasonality of specific pollen types mainly comes from northern hemisphere and developed regions, limiting our ability to extrapolate these findings to other geographical locations. With this research letter, our aim is to contribute to the current knowledge of aerobiology by analyzing the decade-long patterns of airborne tree pollen in the city of Bahia Blanca, Argentina. In general, we found late winter to early spring as the period with the highest Cupressaceae pollen counts. In 2020, the average pollen count during July through September was 78.81 (SD 79.70), the highest recorded during the last 10 years. These months had varying pollen concentrations from moderate (15-89 grains/m3 of air) to high (90-1499 grains/m3 of air). Regardless of such variation, August had consistently been the month with the highest peak concentrations from 2010 to 2020 (61.2, SD 57.3), followed by September (27.1, SD 20.3). We did not find any month with very high (>1500 grains/m3 of air) peak concentration. Further studies need to be done to expand our knowledge on aerobiology to characterize specific pollen sub-types and determine the exact allergenic potential of airborne pollen in different regions.